Pengelolaan Sampah Terintegrasi Ketahanan Pangan di Desa Sukasari Kabupaten Sumedang - Retno Dwi Marwati; Yosep Nurdjaman Alamasyah (UNISBA Press, 2024)
Abstract. Waste is the remains of an item or product that is no longer used. anymore. However, this waste can also be recycled into something that can be useful for human life. useful for human life. If waste is not managed properly, then this waste will become a problem for human life, because this waste can cause the growth of diseases that will attack the human body. can cause the growth of diseases that will attack humans, besides that, this waste will also cause unpleasant odors in our environment. This is certainly a problem for the community environment, because if the local authorities and the community do not move to find a solution, then this is a problem. local officials and the community do not move to find a solution in handling waste, then the threat of disease for the community is already waste, then the threat of disease for the community is in sight. As what happened in Sukasari Village, Sukasari Sub-district, Sumedang Regency. Household garbage that continues to accumulate every day, if there is no serious handling from the village government, then the threat of disease for the community is at hand. serious handling from the village government, then it will become a sharp a sharp bullet to the Public Health of Sukasari village. One of the treatments that must be done by officials and residents is how the garbage can be managed properly, for example recycled so that it becomes a useful product for the life of the village. a product that is useful for the community's life and increases food security for the community. food security for the community. Data collection, both sourced from the results of analysis of KKN students, then information from Sukasari village cadres, and Sukasari villagers. Sukasari villagers, used as data with descriptive analysis method, to realize food security-based waste management for the community. to realize waste management based on food security for community welfare. Abstrak. Sampah adalah sisa-sisa sebuah barang atau produk yang sudah tidak digunakan lagi. Akan tetapi sampah ini juga bisa didaur ulang menjadi sesuatu yang dapat bermanfaat untuk kehidupan manusia. Apabila sampah tidak dikelola dengan baik, maka sampah ini akan menjadi masalah buat kehidupan manusia, karena sampah ini dapat menyebabkan tumbuhnya penyakit yang akan menyerang kepada manusia, selain itu juga sampah ini akan menyebabkan bau yang tidak sedap di lingkungan kita. Hal ini tentunya menjadi masalah bagi lingkungan masyarakat, sebab apabila aparat setempat dan Masyarakat tidak bergerak untuk mencari solusi dalam penanganan sampah, maka ancaman penyakit bagi Masyarakat sudah di depan mata. Seperti halnya yang terjadi di Desa Sukasari Kecamatan Sukasari Kabupaten Sumedang. Sampah-sampah rumah tangga yang setiap hari terus menumpuk, apabila tidak ada penanganan yang serius dari pemerintah desa, maka hal tersebut akan menjadi peluru tajam terhadap Kesehatan Masyarakat desa Sukasari. Salah satu penanganan yang mesti dilakukan oleh aparat dan warga yakni bagaimana caranya sampahsampah tersebut bisa dikelola dengan baik, misalnya didaur ulang sehingga menjadi sebuah produk yang bermanfaat bagi kehidupupan Masyarakat dan meningkatkan ketahanan pangan bagi masyarakat. Pengumpulan data, baik bersumber dari hasil Analisa para mahasiswa KKN, kemudian informasi dari para kader desa Sukasari, dan warga desa Sukasari, dijadikan sebagai data dengan metode deskriptif analisis, untuk mewujudkan pengelolaan sampah yang berbasis ketahanan pangan bagi kesejahteraan Masyarakat.